MODEL FOR IDENTIFICATION AND ANALYSIS OF PROBLEMATIC ISSUES IN THE ACTIVITIES OF OFFICIALS OF THE NATIONAL CENTER FOR ACTION AND MANAGEMENT OF EMERGENCY SITUATIONS OF THE MINISTRY OF EMERGENCY SITUATIONS (American Journal of Interdisciplinary Research and Development, 2022)
In the Ministry of Emergency Situations of the Republic of Uzbekistan, the State System of Prevention of Emergency Situations and Actions in Such Situations (FVDT) of the Republic of Uzbekistan is entrusted with the tasks of organizing management. There are day-to-day management bodies of FVDT to control the operation of subsystems and links of FVDT, as well as to implement operational management within the existing powers.